Perception of character education through heroism lembak ethnic folk story figures - Inda Puspita Sari; Sarwit Sarwono; Agung Nugroho (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The heroism of Lembak ethnic folklore characters is a means of delivering effective character education because the values contained in folklore are very closely aligned with the norms that exist in society. This research aims to describe the perception of character education through the heroism of Lembak ethnic folklore characters in the form of the values of willingness to sacrifice (RB), never give up (PM), love of the homeland (CTA), and solidarity (KK). This study used a descriptive qualitative method. The data collection technique was carried out by carefully reading the entire Lembak ethnic folklore, understanding the sample on the research object, coding the data, compiling the results of the analysis, and making conclusions. Based on the results of the analysis, researchers found that the value of heroism, being willing to sacrifice, the value of never giving up, the value of love for one's country, and value of solidarity arises because of the feeling of affection towards someone by protecting, loyalty, working together and caring for friends, family, lovers, and other people to make it happen. strong solidarity. Based on the research results, it can be concluded that the heroism of the characters in Lembak ethnic folklore, it will provide an overview of character education which can be used as a means of education in society.